الإرشاد الأسري للأطفال ذوي الإعاقة العقلية - طاع الله, حسينة (Sciences de l'Homme et de la Société, 2013)
إن مشاركة أسر الأطفال المعاقين ذهنيًا في برامج الإرشاد التي تعطى للأولياء من قبل المختصين والعاملين في مجال التربية الخاصة، أصبحت ضرورية لتنمية جميع المهارات الأساسية التي تتناسب مع قدراتهم وحاجاتهم البيولوجية والنفسية والتربوية مثل تناول الطعام والمشاركة في الأنشطة الاجتماعية المختلفة، وحسن التصرف في المواقف المعايشة عن طريق التقليد والدعم،  فيؤدي بهم إلى الاستقلالية الذاتية والاجتماعية والمهنية.   The participation of the parents of the mentally disabled children in the guidance programmes prepared by the professionals of Special Education becomes crucial to develop the basic skills needed by this category (the mentally disabled children) that are commensurate with their abilities and also with their psychological, educational and biological needs such as: how to eat, how to participate in different social activities and how to acquire an adequate behaviour to deal with the various situations lived, this can be achieved through imitation and support that would lead these mentally disabled children to self reliance in different fields.